Monitoring the Water Bodies of the Mackenzie Delta by Remote Sensing Methods - Mouchot, Marie-Catherine; Alfoldi, Thomas; De Lisle, Daniel; McCullough, Greg (ARCTIC, 1991)
In the Mackenzie Delta, Northwest Territories, the thousands of lakes, ponds, channels and waterways, connected in an apparently chaotic manner, present a major logistical problem for collecting information regarding the nature of this complex hydrologic system. The use of satellite images gives an economical and synoptic view of this isolated region, while special analysis techniques simplify the environmental appraisal. The use of (mathematical) morphological analysis of the surface waters imaged by the satellite allowed the authors to distinguish all water bodies, even when they were at the limit of the spatial resolution of the sensor. The technique further permitted the classification of these water bodies by their inter- and intra-connectivity. Another technique, termed chromaticity analysis, allows for the removal of atmospheric differences among images, which in turn enables the use of surface calibration data from one date to be used on images of other dates. This method was also used to generate quantitative maps of suspended sediment concentration levels. Together, these techniques permit the assessment of the hydrologic flow (or its hindrance) of sediment and nutrients for the sustenance of aquatic flora and fauna. They further supply a method for the mapping of access routes by water craft to all parts of the Delta.Key words: mathematical morphology, chromaticity analysis, remote sensing, Landsat, Mackenzie Delta, suspensdeeddi ment, hydrologic network Mots clés: morphologie mathématique, analyse par chromaticité, télédétection, Landsat, Delta du Mackenzie, sediments en suspension, réseau hydrologique